The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1089/gtmb.2015.0213
|View full text |Cite
|
Sign up to set email alerts
|

ATP7B Gene Mutations in Croatian Patients with Wilson Disease

Abstract: Clinical diagnosis of WD was confirmed in 59 patients by detecting mutations on both ATP7B alleles. The age at onset of WD and the type of WD clinical presentation showed no significant correlation with the ATP7B genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Despite the biological rationale that the type of mutation in the DNA leads to a deformation in the protein, this observation is not linear in WD. In some studies, age at WD onset and type of clinical presentation did not show a significant correlation with ATP7B genotype [12,13] .…”
Section: Discussionmentioning
confidence: 91%
“…Despite the biological rationale that the type of mutation in the DNA leads to a deformation in the protein, this observation is not linear in WD. In some studies, age at WD onset and type of clinical presentation did not show a significant correlation with ATP7B genotype [12,13] .…”
Section: Discussionmentioning
confidence: 91%
“…Forbes et al [ 20 ] has given evidence for the effects of ATP7B mutations in severe neuropsychiatric deterioration. Ljubic et al [ 21 ] indicated that mutations in the P-domain interfered with catalytic phosphorylation. In addition, this mutation was compounded by the heterozygous mutation c.2866-2A > G located in the splice site, which can affect mRNA splicing [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wilson's disease (WD), also known as hepatolenticular degeneration, is an autosomal recessive disorder of copper metabolism caused by an ATP7B gene mutation 1 . WD results in a decrease in copper excretion in bile, which leads to the accumulation of copper in various organs, including the liver and brain, causing liver, and nerve damage, and mental symptoms 2 . While the clinical manifestations of WD patients involve multiple systems, liver disease is most prevalent, and is more common in younger children.…”
Section: Introductionmentioning
confidence: 99%